2004
DOI: 10.1002/cncr.20253
|View full text |Cite
|
Sign up to set email alerts
|

Second neoplasms in pediatric patients with primary central nervous system tumors

Abstract: BACKGROUNDDetails on second neoplasms (SNs) following pediatric central nervous system (CNS) tumors are scant, because of the rarity of such SNs. The goal of the current study was to investigate and characterize these rare SNs.METHODSThe authors reviewed clinical and treatment data on all institutional patients age < 22 years at diagnosis of a primary CNS tumor who developed any type of SN. Patients with neurofibromatosis type 1 were excluded. Cumulative incidence rates were estimated, and putative risk fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(57 citation statements)
references
References 34 publications
1
56
0
Order By: Relevance
“…[1][2][3][4][5] The cranial irradiation, especially the radiation dose and the field size, is known as the significant risk factor for developing second brain neoplasms. 1,[6][7][8][9][10][11] However, details of this relationship are still not clear.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] The cranial irradiation, especially the radiation dose and the field size, is known as the significant risk factor for developing second brain neoplasms. 1,[6][7][8][9][10][11] However, details of this relationship are still not clear.…”
mentioning
confidence: 99%
“…Since their 3 cases, there have been 17 additional cases, including this report, of primary CPC, occurring in patients with LFS/LFL, germline TP53 mutations, or both [12, 13, 15, 29,45,46,47,48,49,50]. The number of such cases may be underestimated since many reports do not distinguish between types of CNS tumors or divide CPTs into papillomas and carcinomas [1,2,3,4,5, 23, 25, 26, 51, 52].…”
Section: Discussionmentioning
confidence: 99%
“…We know that pe diatric patients with primary malignant brain tumors who received radiation therapy have an increased risk of devel oping a secondary malignant neoplasm, the majority of which are brain tumors and include meningioma, glioblas toma, and anaplastic astrocytoma. 4,6 Studies have shown a high rate of mortality associated with secondary gliomas, but a high survival rate of secondary meningiomas. 4 The utility of screening for recurrent medulloblasto ma remains controversial, especially in the absence of es tablished effective salvage therapies; however, as current protocols still recommend routine surveillance scanning, the physician must be prepared to critically interpret posi tive results.…”
Section: Fig 3 Axial Mri Flair Image Demonstrating Abnormal Signal mentioning
confidence: 99%
“…4,6 Studies have shown a high rate of mortality associated with secondary gliomas, but a high survival rate of secondary meningiomas. 4 The utility of screening for recurrent medulloblasto ma remains controversial, especially in the absence of es tablished effective salvage therapies; however, as current protocols still recommend routine surveillance scanning, the physician must be prepared to critically interpret posi tive results. As we have illustrated, caution must be taken when basing the diagnosis of recurrent medulloblastoma on symptomatology and MRI alone.…”
Section: Fig 3 Axial Mri Flair Image Demonstrating Abnormal Signal mentioning
confidence: 99%